Transcranial Doppler Ultrasound During Critical Illness in Children: Survey of Practices in Pediatric Neurocritical Care Centers*. Issue 1 (January 2020) - LaRovere, Kerri L.; Tasker, Robert C.; Wainwright, Mark; Reuter-Rice, Karin; Appavu, Brian; Miles, Darryl; Lidsky, Karen; Vittner, Patrick; Gundersen, Daniel; O'Brien, Nicole F.
Abstract : Objectives: The scope of transcranial Doppler ultrasound in the practice of pediatric neurocritical care is unknown. We have surveyed pediatric neurocritical care centers on their use of transcranial Doppler and analyzed clinical management practices. Design: Electronic-mail recruitment with survey of expert centers using web-based questionnaire. Setting: Survey of 43 hospitals (31 United States, 12 international) belonging to the Pediatric Neurocritical Care Research Group. Patients: None. Interventions: None. Measurements and Main Results: A 67% (29/43) hospital-response rate. Of these centers, 27 reported using transcranial Doppler in the PICU; two hospitals opted out due to lack of transcranial Doppler availability/use. The most common diagnoses for using transcranial Doppler in clinical care were intracranial/subarachnoid hemorrhage (20 hospitals), arterial ischemic stroke (14 hospitals), and traumatic brain injury (10 hospitals). Clinical studies were carried out and interpreted by credentialed individuals in 93% (25/27) and 78% (21/27) of the centers, respectively. A written protocol for performance of transcranial Doppler in the PICU was available in 30% (8/27 hospitals); of these, two of eight hospitals routinely performed correlation studies to validate results. In 74% of the centers (20/27), transcranial Doppler results were used to guide clinical care: that is, when to obtain a neuroimaging study (18 hospitals); how to manipulate cerebral perfusion pressure with fluids/vasopressors (13 hospitals); and whether to perform a surgical intervention (six hospitals). Research studies were also commonly performed for a range of diagnoses. Conclusions: At least 27 pediatric neurocritical care centers use transcranial Doppler during clinical care. In the majority of centers, studies are performed and interpreted by credentialed personnel, and findings are used to guide clinical management. Further studies are needed to standardize these practices. Abstract : Supplemental Digital Content is available in the text.